Kesalehan ‘Alawi dan Islam di Asia Tenggara - Zulkifli, Zulkifli (Studia Islamika, 2016)
Chiara Formichi and R. Michael Feener, eds. 2015. Shi‘ism in Southeast Asia: ‘Alid Piety and Sectarian Constructions. London: Hurst & Company.Sunni and Shi’i studies have thus far been conducted along existing sectarian lines. But this volume edited by Formichi and Feener is an attempt to depart from that long-lasting academic tradition. Assuming the continuous tradition of Hodgson’s ‘Alid loyalism, the book intends to develop the assessment and analysis of diverse elements of ‘Alid piety among Muslims in Southeast Asia. The use of ‘Alid piety as the conceptual framework is path-breaking work in the academic study of Southeast Asian Islam, because this concept transcends Sunni and Shi‘i sectarian identities. The book tries to trace the historical foundation of ‘Alid piety in Southeast Asia, its manifestation in literary legacies, its modalities and cultural expressions, and contemporary developments in the sectarian construction. However, it would have provided more comprehensive and nuanced understanding of elements of ‘Alid piety if certain aspects of popular Sufi and religious tradition, particularly the celebration of the Prophet Muhammad’s birthday, were included.DOI: 10.15408/sdi.v23i3.3344